Moses and Christ in the Wilderness Narrative: Transformation of Religious Traditions in 1 Cor 10 - Sin Pan Ho (Religions, 2023)
Unlike Islam, Judaism and Christianity, religions in antiquity were non-confessional and lacked moral instructions for worshippers. Patron–client associations seemed to depict gods-worshipper relations in Paul’s time. In this paper, I argue that Paul in 1 Cor 10:1–4 uses both his former religious traditions and those of the first audience, Jews and non-Jews, to convince them about his novel God–Christ patron–covenant theology. Paul abruptly introduced Moses (10:2), spiritual food/drink (10:3–4a) and Christ (10:4b) into the classic Jewish wandering story in the wilderness to delineate his anti-idol rhetoric throughout 1 Cor 10. Paul paradoxically warned the first audience against their idol-worshipping lifestyles by utilising and transforming Jewish Shema worship into a binitarian God–Christ covenantal relation, and idol-worship traditions to the only patron family god of the Christ-follower community. Paul’s rhetorical purpose of (re)introducing the concept of God as Moses’ God and Christ as an anti-idol polemic is a coherent theme throughout 1 Cor 10 and probably throughout 1 Cor 11–14.